Pengaruh Motivasi Kerja, Kepuasan Kerja, Kedisiplinan Dan Kepemimpinan Terhadap Kinerja Karyawan Di Kantor Balai Besar Wilayah Sungai Bengawan Solo - Agustina, Nilla Dyah, Drs. Wiyadi, MM., Ph.D, Drs. M. Farid Wajdi, MM., Ph.D (2016)
The purpose of this study was to significant effect analysis: 1)work motivation to employee performance in Bengawan Solo River Region Big Hall Office 2) work satisfaction to employee performance in Bengawan Solo River Region Big Hall Office. 3) work discipline to employee performance in Bengawan Solo River Region Big Hall Office. 4) Leadership to employee performance in Bengawan Solo River Region Big Hall Office. Appropriate objectives so this study was using quantitative by survey method approach. This research population was all of employee in Bengawan Solo River Region Big Hall Office. Sample was taking 120 persons by using simple random sampling technique. The main data collection tool using a questionnaire developed by the researchers and tested for validity and reliability in order to qualify a good measuring tool. Analysis tools used to test this hypothesis using Multiplled Regresion Analysis using SPSS 21.0 for Windows. Results of this study concluded: 1) Excelsior assess the responder perception to work motivation hence excelsior also employees performance in Bengawan Solo River Region Big Hall Office. 2) Excelsior assess the responder perception to work satisfaction hence excelsior also employees performance in Bengawan Solo River Region Big Hall Office. 3) Excelsior assess the responder perception to work discipline hence excelsior also employees performance in Bengawan Solo River Region Big Hall Office. 4) Excelsior assess the responder perception to leadership hence excelsior also employees performance in Bengawan Solo River Region Big Hall Office. 5)work motivation, work satisfaction, work discipline and leadership have an effect simultaneous to employee performance in Bengawan Solo River Region Big Hall Office, was proven from F count value (12,798) > Ftable (2,45). 6) motivation, work satisfaction, work discipline and leadership was giving the effect equal to 30,8% to employee performance in Bengawan Solo River Region Big Hall Office, was proven from coefficient determination value (R2) equal to 0,308.